Non-pharmaceutical Interventions for Hypertrophic Cardiomyopathy: A Mini Review - He, Miaomiao; Qiu, Jie; Bai, Yang; Wang, Yan; Hu, Mei; Chen, Guangzhi (Frontiers in Cardiovascular Medicine, 2021)
Hypertrophic cardiomyopathy is an inherited cardiovascular disease, and 70% of patients have left ventricular outflow tract obstruction. Ventricular septal myectomy has been the gold standard treatment for most patients with refractory symptoms. Due to higher mortality associated with medical facilities with less experience, alcohol septal ablation has been accepted as an alternative to conventional surgical myectomy. It offers lower all-cause in-hospital complications and mortality, which could be potentially more preferable for patients with serious comorbidities. In recent years, radiofrequency ablation, providing another option with reproducibility and a low risk of permanent atrioventricular block, has become an effective invasive treatment to relieve left ventricular outflow tract obstruction. Moreover, substantial progress has been made in gene therapy for hypertrophic cardiomyopathy. The principal objective of this review is to present recent advances in non-pharmaceutical interventions in hypertrophic cardiomyopathy.